Prevalence and risk factors for Chlamydia trachomatis, Neisseria gonorrhoeae and Trichomonas vaginalis infection in pregnant women in Papua New Guinea. (13th October 2014) - Wangnapi, R A; Soso, S; Unger, H W; Sawera, C; Ome, M; Umbers, A J; Ndrewei, N; Siba, P; Li Wai Suen, C S N; Vallely, A; Wapling, J; Ryan, C; et al.
Abstract : Objective: To determine the prevalence of, and risk factors associated with, Chlamydia trachomatis, Neisseria gonorrhoeae and Trichomonas vaginalis infection in pregnant women in Madang, Papua New Guinea (PNG). Methods: A cross-sectional survey was conducted among 400 pregnant women presenting to antenatal clinics. Sociodemographic and behavioural data were collected and real-time PCR diagnostic methods were used to detect the presence of chlamydia, gonorrhoea and trichomonas in self-collected vaginal swabs. The relationships between symptoms, sociodemographic and behavioural factors and infection were assessed. Results: The prevalence of C. trachomatis was 11.1%, N. gonorrhoeae was 9.7% and T. vaginalis was 21.3%. One-third of women (33.7%) had at least one infection. The most common symptom was abdominal pain (48.0%), but only abnormal vaginal discharge was consistently associated with infection (p<0.001). Women diagnosed with vaginal discharge syndrome were more likely to have at least one treatable infection (50.0% (47/94) vs 26.8% (68/254), p<0.001), yet 59.1% of women with infection would have been missed by the current clinically-based syndromic diagnosis. Risk factors included having a partner at perceived risk of infection, maternal extramarital intercourse, early sexual debut, lack of formal education, urban residence and smoking. 78.8% of women reported never using condoms. Conclusions: The prevalences of T. vaginalis, C. trachomatis and N. gonorrhoeae were high among pregnant women in coastal PNG. The poor performance of clinically based syndromic diagnosis suggests that alternative strategies are urgently required to improve detection and reduce the burden of sexually transmitted infections and their associated adverse pregnancy outcomes in this population.